Constructing global order : agency and change in world politics - Acharya, Amitav (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2018)
"For a long time, international relations scholars have adopted a narrow view of what is global order, who are its makers and managers, and what means they employ to realize their goals. Amitav Acharya argues that the nature and scope of agency in the global order - who creates it and how - needs to be redefined and broadened. Order is built not by material power alone, but also by ideas and norms. While the West designed the post-war order, the non-Western countries were not passive. They contested and redefined Western ideas and norms, and contributed new ones of their own making. This book examines such acts of agency, especially the redefinitions of sovereignty and security, shaping contemporary world politics. With the decline of Western dominance, ideas and agency from the Rest may make it possible to imagine and build a truly global order"--
"For a long time, international relations scholars have adopted a narrow view of what is global order, who are its makers and managers, and what means they employ to realize their goals. Amitav Acharya argues that the nature and scope of agency in the global order - who creates it and how - needs to be redefined and broadened. Order is built not by material power alone, but also by ideas and norms. While the West designed the post-war order, the non-Western countries were not passive. They contested and redefined Western ideas and norms, and contributed new ones of their own making. This book examines such acts of agency, especially the redefinitions of sovereignty and security, shaping contemporary world politics. With the decline of the Western dominance, ideas and agency from the Rest may make it possible to imagine and build a truly global order. Amitav Acharya is Distinguished Professor of International Relations and the UNESCO Chair in Transnational Challenges and Governance at the School of International Service, American University, Washington, DC. His recent books include: The End of American World Order (2014); Rethinking Power, Institutions and Ideas in World Politics: Whose IR (2014); Whose Ideas Matter: Agency and Power in Asian Regionalism (2009) and Why Govern: Rethinking Demand and Progress in Global Governance (edited 2016). He is the first non-Western scholar to be elected as the President of the International Studies Association (ISA)"--
Machine generated contents note: 1. Introduction: rethinking agency and change in global order; 2. Theorizing normative change; 3. Provincializing Westphalia; 4. Transforming Westphalia; 5. Redefining security; 6. Regionalism and the making of global order; 7. Conclusion and extensions.
Includes bibliographical references and index.
School of General Education
Keywords: International organization; East and West; Agent (Philosophy); Nonwestern countries; Social sciences